Tracking of physical activity and sedentary behavior of adolescents in different domains - Gustavo Aires de Arruda; Francys Paula Cantieri; Diogo Henrique Constantino Coledam; Diego Giulliano Destro Christofaro; Mauro Virgilio Gomes de Barros; Jorge Mota; Fatima Maria da Silva Abrão; Arli Ramos de Oliveira (Universidade Estadual de Maringá, 2022)
This study aimed to verify the tracking of physical activity and sedentary behavior in different domains during adolescence. This longitudinal study involved 265 subjects (boys: 52.8%) with an initial mean age of 13.9 (± 1.2) years. Physical activity and sedentary behavior were verified using a questionnaire. The achievement of ≥ 150 min. week-1 of moderate-to-vigorous intensity sport and/or physical exercise for ≥ 1 month was adopted as sufficiently active. The data were collected on 2 occasions, with an average interval of 3 years. The description of the results used the relative frequency and Binary Logistic Regression was used to estimate the crude and adjusted odds ratios (95% confidence intervals). Current physical activity (adjusted odds ratios = 3.05; 95% confidence intervals: 1.77 - 5.26) and sedentary behavior (adjusted odds ratios = 1.81; 95% confidence intervals: 1.03 - 3.19) appear to be significantly influenced by previous behavior, except for light-intensity physical activity. Only 12.8% of the participants remained sufficiently active for sport and/or physical exercise. Practice for at least one month of sport and/or physical exercise at baseline was a predictor of practice in the follow-up, both considering participation for at least one month (adjusted odds ratios = 2.81; 95% confidence intervals: 1.37 - 5.79) and for four months (adjusted odds ratios = 2.47; 95% confidence intervals: 1.17 - 5.24) in the follow-up. Being sufficiently active at baseline increased the chance of being sufficiently active in the follow-up during adolescence. Interventions providing sufficient sport and/or physical exercise could positively influence the chances of practice in the future. For light-intensity physical activity interventions, strategies targeting adherence seem especially relevant